2009
DOI: 10.1097/hcr.0b013e3181b4ca27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cardiac Rehabilitation With Relaxation Therapy on Psychological, Hemodynamic, and Hospital Admission Outcome Variables

Abstract: Relaxation therapy was associated with a positive effect on psychological stress and hemodynamic variables beyond that promoted by cardiac rehabilitation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(32 reference statements)
1
20
0
Order By: Relevance
“…This finding is consistent with the works of Neves [12] whose work concluded that patients who participated in relaxation therapy improved their cardiovascular risk factors profile. This findings is also consistent with findings of van Dixhoorn et al and Collins and Rice [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…This finding is consistent with the works of Neves [12] whose work concluded that patients who participated in relaxation therapy improved their cardiovascular risk factors profile. This findings is also consistent with findings of van Dixhoorn et al and Collins and Rice [13,14].…”
Section: Discussionsupporting
confidence: 82%
“…A relaxation program reduces cardiac mortality and morbidity, and has a favourable effect on physical, psychological and social parameters (including resting heart rate and fear of exercise) (Level 1) [35], and appears to be superior in combination with an exercise program compared with only an exercise program (level 2) [36]. …”
Section: Resultsmentioning
confidence: 99%
“…• The duration of follow-up was less than 6 months (e13). The 20 full-text articles (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) that were eventually included reported the results of 12 randomized trials with a total of 1085 patients.…”
Section: Literature Surveymentioning
confidence: 99%